1983
DOI: 10.1161/01.cir.67.1.134
|View full text |Cite
|
Sign up to set email alerts
|

Aneurysmal coronary artery disease.

Abstract: To examine the clinical and historical features and the natural history of aneurysmal coronary disease, we reviewed the registry data of the Coronary Artery Surgery Study (CASS). Nine hundred seventy-eight patients, representing 4.9% of the total registry population, were identified as having aneurysmal disease. No significant differences were noted between aneurysmal and nonaneurysmal coronary disease patients when features such as hypertension, diabetes, lipid abnormalities, family history, cigarette consump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

24
831
8
47

Year Published

1989
1989
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 883 publications
(910 citation statements)
references
References 17 publications
24
831
8
47
Order By: Relevance
“…This finding agrees with the results published in several previous studies, in which it has been widely shown that CAE co-exists with CAD approximately in 85% of cases [3,[13][14][15][16][17]. The right coronary artery was the most involved artery in the coronary artery ectasia followed by the anterior descending artery and the circumflex artery [2,13,18,19].…”
Section: Discussion:-supporting
confidence: 91%
“…This finding agrees with the results published in several previous studies, in which it has been widely shown that CAE co-exists with CAD approximately in 85% of cases [3,[13][14][15][16][17]. The right coronary artery was the most involved artery in the coronary artery ectasia followed by the anterior descending artery and the circumflex artery [2,13,18,19].…”
Section: Discussion:-supporting
confidence: 91%
“…CAE has been defined as localized or diffuse non-obstructive lesions of one epicardial coronary artery with a luminal dilatation exceeding the 150% of a normal adjacent vessel diameter [4]. It is characterized by an abnormal dilatation of coronary artery, represents a form of atherosclerotic coronary artery disease, seen in 3-8% of patients undergoing coronary angiography [1].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Guy et al showed increased prevalence of CAE in patients with abdominal aortic aneurysms (10). Most risk factors of CAE are similar to coronary artery stenosis (CAS), including cigarette smoking, male gender, hypertension (HTN), positive family history of coronary artery disease, elevated CRP and hyperhomocysteinemia (2,(11)(12)(13). Interestingly, diabetes mellitus (DM) is significantly lower in CAE patients in comparison to CAS group (11,14).…”
Section: Introductionmentioning
confidence: 99%